When the Flower Wilts: Stigmas of Mental Illnesses in Indonesia - Shella Novia Herada (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
In Indonesia, mental illnesses, or more specifically, depression, is still seen as a moral failure, a failure to conform in society due to a faulty moral upbringing. However, little spotlight is given towards the immediate family of a sufferer, how a sufferer places burdens on their family in terms of economy, psychology, and social life, in addition to the burden of sympathy as the result of having to put the needs of someone else above onself. To depict such suffering and help make it more visible, I created a story, written from the perspective of someone close to a sufferer, to show how the immediate family also suffers from the negative stigma attached to a sufferer. Keywords: sufferer, burden of sympathy, depression.